An evaluation of a Transition to Foundations curriculum for first year pediatric residents in Competency Based Medical Education (Canadian Medical Education Journal, 2023)
Implication StatementA Transition to Foundations (TTF) curriculum that includes didactic and simulation components prepares first-year pediatric residents for increased roles and responsibilities in the Foundations of Discipline stage of Competency Based Medical Education, including junior night float rotations. Simulations of acute presentations improve resident comfort before overnight on-call experiences.